Pelaksanaan Program Ciri Khusus Keasramaan Boarding School dalam Menambah Wawasan Keislaman di Madrasah Aliyah Negeri 2 Surakarta - Pratama Ananda Ayu Nur Fadhilah; Siti Choiriyah (Syntax Corporation Indonesia, 2024)
The role of parents in instilling an understanding of Islamic teachings to children who are still low has an impact on the lack of awareness of children in practicing Islamic teachings in life. The existence of this phenomenon is the basis for the boarding school MAN 2 Surakarta to have a special characteristic program that aims to add Islamic insight for students. This study aims to describe the forms of special characteristics program activities and describe the implementation of the special characteristics program of boarding school girls in adding Islamic insight at Madrasah Aliyah Negeri 2 Surakarta.